Serebryanska M., Latkovska J.S. Functioning of impersonal verbal forms in journalistic texts - Serebryanska M.; Latkovska J. S. (Philological Treatises, 2020)
The article deals with analysis of functioning of impersonal verbal forms in the mass media language on the basis of Ukrainian newspapers “Ukraina moloda” («Young Ukraine») and «Sumshchyna” (“Sumy Region”). It focuses on semantic groups and communicative functions of these verbs.